On Common Fixed Point Theorems for Hybrid Mappings Satisfying Contractive Condition of Higher Degree and (CLR) Properties - Rao, V. Sambasiva; Dixit, Uma (Communications in Mathematics and Applications, 2022)
In this study, we adopt an inequality of higher degree to acquire common fixed points for single and multi valued mappings with the help of (CLR) and (JCLR) properties. All of our results are strengthened with suitable examples.